The mediating role of economic sustainability and crisis environment in the relationship between CSR initiatives and customer satisfaction - Zaw, Wai Yan Paing; Rojniruttikul, Nuttawut; Chaveesuk, Singha (My University, 2026)
This study examines how corporate social responsibility (CSR) initiatives relate to customer satisfaction in Myanmar’s private banking sector by testing economic sustainability and the crisis environment as proposed mediating mechanisms and the crisis environment as a moderating condition. Using a quantitative survey of private bank customers in Myanmar and structural equation modeling (SEM), the study evaluates direct, indirect, and moderating relationships. The findings show that CSR Initiatives significantly predict Economic Sustainability and Crisis Environment, indicating that CSR contributes to stability- and crisis-related perceptions within the banking context. However, CSR Initiatives do not have a significant direct effect on Customer Satisfaction, and the overall bootstrapped indirect effect is not statistically supported. In contrast, Crisis Environment has a positive and statistically significant direct effect on Customer Satisfaction (β = 0.116, p = 0.026). Moderation analysis further shows that Crisis Environment strengthens the relationship between CSR and Customer Satisfaction, although the interaction effect is small (β = 0.068). These results suggest that CSR is better understood as a context-sensitive signal than as a broad direct or mediated driver of customer satisfaction. The model explains a moderate proportion of variance in Customer Satisfaction (R2 = 0.460), indicating that crisis-related perceptions play a more prominent role than CSR’s direct or indirect effects in shaping customer satisfaction in this setting. Overall, the study contributes to CSR research by showing that, in a volatile emerging-market context, CSR matters more under crisis conditions than as a general predictor of customer satisfaction.
Keywords: banking sector; Corporate social responsibility (CSR); crisis environment; customer satisfaction; economic sustainability; Myanmar